Rhizobacterial consortium mediated aroma and yield enhancement in basmati and non-basmati rice ( Oryza sativa L.) - Dhondge, Harshal V.; Pable, Anupama A.; Barvkar, Vitthal T.; Dastager, Syed G.; Nadaf, Altafhusain B. (Journal of Biotechnology, 2021)
Basmati and non-basmati rice varieties are commercially important. Aromatic rice varieties are low yielding and recently depletion in aroma is observed due to the shift towards modern agriculture. Therefore, it is necessary to restore the aroma and increase the yield through sustainable agriculture. The use of microbial bioinoculants is one of the promising ways to achieve these targets. With these objectives, rhizospheric bacterial strains Enterobacter hormaechei (AM122) and Lysinibacillus xylanilyticus (DB25) having the property of synthesizing 2acetyl-1-pyrroline (2AP) were isolated from the rhizosphere of two aromatic rice varieties, Ambemohar-157 and Dehradun Basmati respectively and their effect on plant growth, aroma and yield enhancement under mono-inoculation and consortium conditions was analyzed. The bacterial inoculum in consortium resulted in significant improvement in vegetative growth, yield and 2AP content over mono inoculation and control. The study highlights the potential of E. hormaechei and L. xylanilyticus in plant growth, yield and aroma enhancement in basmati and non-basmati rice varieties. These strains can be taken up further for developing a commercial bioformulation.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice; Non-basmati rice; plant growth promotion; Rhizosphere; yield

Exploring the core microbiota in scented rice (Oryza sativa L.) rhizosphere through metagenomics approach - Dhondge, V. Harshal; Barvkar, Vitthal T.; Paul, Dhiraj; Dastager, Syed G.; Pable, Anupama A.; Nadaf, Altafhusain B. (Microbiological Research, 2022)
Rice is a major food crop cultivated around the globe. Specially scented rice varieties are of commercial importance but they are low-yielding. The rhizospheric microflora plays a significant role in improving yield and aroma. However, the core microbiome of the scented rice rhizosphere is comparatively less explored. Here, we analyzed the core microbiome associated with the rhizosphere of the scented (Ambemohar-157 and Dehradun basmati) in comparison with non-scented rice (Kolam and Arize 6444 Gold) cultivated at two different geoclimatic zones of India (Maharashtra and Uttarakhand) using the metagenomics approach. The alpha and beta diversity analysis showed that the microbial communities associated with scented and non-scented varieties significantly changes with respect to richness, diversity, and evenness. The taxonomic profiling revealed the variation in composition, diversity, and abundance of the microbiome in terms of phyla and genera associated with scented rice varieties over non-scented. The cluster analysis distinguishes the microbial communities based on their geographical positions. The core microbiome analysis revealed that scented rice rhizosphere shelters distinct and unique microbiota. 28.6 % of genera were exclusively present only in the scented rice rhizosphere. The putative functional gene annotation revealed the high abundance of genes related to the biosynthesis of 2-acetyl-1-pyrroline (2AP) precursors in scented rice. The precursor feeding analysis revealed proline as a preferred substrate by 2AP synthesizing bacteria. The 2AP precursor proline and proline metabolism genes showed a positive correlation. The scented rice-specific rhizobacteria pointed out in this study can be used as bioinoculants for enhancing aroma, yield, and sustainable rice cultivation.
Keywords: Metagenome; Microbial community; Microbiome; Oryza sativa; Rhizosphere; rice

Seasonal dynamics and tree foliar habit drive the rhizobacterial diversity in congeneric Ficus species from Northern Western Ghats, India - Salunkhe, Vaishnavi H.; Kunte, Pooja S.; Paul, Dhiraj; Kasodekar, Amol K.; Kadoo, Narendra Y. (Rhizosphere, 2023)
Tree species, annual climatic cycle, and geochemical properties influence the tree rhizospheric microbiome. However, its understanding in the moist deciduous forest of Northern Western Ghats (NWG), India, is limited. Moreover, the effects of foliar habits of trees and seasonal variations on rhizobacterial communities across congeneric tree species are unexplored. Hence, we employed high throughput 16 S rRNA gene sequencing to examine the effects of foliar habits of congeneric tree species and seasonal influences on the rhizobacterial community. For this study, rhizospheric soil from Ficus arnottiana (deciduous) and Ficus talboti (evergreen) trees from NWG, India, was collected during three seasons (summer, monsoon, and winter) and subjected to high throughput sequencing. A total of 3031 amplicon sequence variants (ASV) were observed, of which 1257 and 1181 ASV were unique to F. arnottiana and F. talboti, respectively, and 593 ASV were common to both species. The phyla Actinobacteria, Proteobacteria, Acidobacteria, and Chloroflexi were ubiquitous and contributed >90% to the rhizobacterial community. Some bacterial phyla were exclusively associated with either of the tree species and seasons. Different bacterial phyla performed similar functions in different seasons, indicating their functional redundancy and emphasizing their resilience and adaptability across seasons. It was observed that seasonal dynamics mainly drove the rhizobacterial diversity; however, it was also influenced by the foliar habits of the trees and geochemical properties. The study enhances the understanding of congeneric tree microbiomes and offers valuable insights into their potential applications through microbiome engineering.
Keywords: Amplicon variants; Bacterial diversity; Ficus arnottiana; Ficus talboti; Rhizosphere